Atlas of 3D Transesophageal Echocardiography in Structural Heart Disease Interventions Cases and Videos - Hsiung, Ming-Chon (Springer Singapore, 2018)
This book introduces classic and unique cases in 3D TEE in structural heart disease interventions. In each all the 40 cases, background information, clinical presentations, and diagnostic findings are present and followed by step-by-step approaches of interventional therapies and outcomes after the procedures. The highlight of the book is to utilize extensive illustrations, over 500, to demonstrate various cardiovascular pathologies. Most of the figures are 3D transesophageal echocardiograms, they are cooperated with 2D transesophageal echocardiograms, X rays, fluoroscopies, computed tomograms, etc. Since the echo images obtained in clinic practice are moving images, it also includes over 300 videos, which serve as a supplement to the static illustrations in this book. The atlas is organized into five chapters. In Chapters one, cases received closure of congenital and acquired cardiac defects are described. Transcatheter aortic valve implantation and its complications are discussed in Chapter two and three. Chapter four details the valve-in-valve therapy. Chapter five covers MitraClip therapy. It offers readers an insider's view of 3D transesophageal echocardiography in structural heart disease interventions and to refresh their clinical work.